Morphological, phylogenetic, and genomic evidence reveals the causal agent of thread blight disease of cacao in Peru is a new species of Marasmius in the section Neosessiles, Marasmius infestans sp. nov. - Huamán Pilco, Ángel Fernando (2023)
The thread blight disease (TBD) of cacao (Theobroma cacao) in the department of Amazonas, Peru was recently reported to be caused by Marasmius tenuissimus (Sect. Neosessiles). This same species is known to be the main causal agent of TBD in West Africa. However, some morphological characteristics, such as the presence of rhizomorphs, the almost exclusively white color, and pileus sizes less than 5 mm, among others, differ to the description of M. tenuissimus. Therefore, we aimed to conduct a taxonomic revision of the cacao-TBD causal agent in Peru, by using thorough micro and macro morphological, phylogenetic, and nuclear and mitochondrial genomic approaches. We showed that the causal agent of TBD of cacao in Amazonas, Peru, belongs to a new species, Marasmius infestans sp. nov. This study enriches our knowledge of species in the Sect. Neosessiles, and strongly suggests that the M. tenuissimus species complex is highly diverse.